Implementation of Wallace's Creative Process in Learning Batik through the Splash Technique for Elementary Education Students - Asrivi, Queen Elvina Sevtivia (Journal of Integrated Elementary Education, 2025)
Batik is significant in Indonesian culture and is recognized by UNESCO as an intangible cultural heritage. However, students of the elementary education department (PGMI) have a limited grasp of the batik-making process. This research aims to clarify the creative steps involved in producing batik using the splash technique, as practiced by PGMI IBN Tegal students during their Art Practice course. The study utilized a descriptive qualitative approach to gather data. Semi-structured interviews were conducted with the students and the batik entrepreneur, Nur Elza. Additionally, direct observations and documentation were incorporated into the research process. To analyze the data, we employed the interactive model developed by Miles and Huberman, ensuring the validity of our findings through the triangulation of various techniques and sources. The results indicate that the creative process, as detailed by Wallace regarding the splash technique in batik, encompasses several stages: preparation, incubation, illumination, and verification. Each stage provides students with both theoretical insights and practical experience in splashing batik techniques, thereby enhancing the competencies of future elementary school teachers to better respond to the dynamic landscape of education in Indonesia. Furthermore, the collaborative learning approach with a resource person has resulted in heightened student engagement, positively impacting learning outcomes and achievements. Students exhibited more significant effort, persistence, and enthusiasm while undertaking the challenge of creating batik using the splash technique. This experience has also expanded their understanding of Tegalan Batik, characterized by its unique attributes distinct from other regional styles, significantly enriching their learning experience in the Art Practice course.